مرسل واقعات سیرت سے فقہی احکام پر استدلال امام ابو عبیدؒ کا کتاب الاموال میں منہج: Jurisprudential reasoning over Sirah events Imam Abu Ubaid Qasim bin Sallam’s research-based approach in book “Al-Amwal” - Abdul Ghaffar,; Prof. Dr. Shah Moeen ud Din Hashmi, (Al Manhal Research Journal, 2024)
Sunnah is one of the basic sources of Islamic Jurisprudence. The category of Sunnah is not only limited to the sources of hadith books, but the incidents of Sirat are also frequently used for jurisprudential reasoning by the Jurists. Among them is the renowned scholar Imam Abu Ubaid who stands on the position of a Mujtahid. In his valuable book “Al-Amwal” he has been using Sirat incidents for reasoning along with other sources. Besides, some of these incidents are of the category of Mursal. However, the acceptability of the Mursal narrations is a matter of dispute among Muhaddithin and Jurists. The former do not consider it reliable. The later do accept it but with conditions and limitations. Since Abu Ubaid is among the pioneer Jurists, it is quite significant to study his way of using Mursal narrations in jurisprudential reasoning. The article is a study of his approach towards using and avoiding Mursal narrations.